Recurrence of cutaneous melanoma of the head and neck after negative sentinel lymph node biopsy. Issue 8 (11th July 2014) - Davis–Malesevich, Melinda V.; Goepfert, Ryan; Kubik, Mark; Roberts, Dianna B.; Myers, Jeffrey N.; Kupferman, Michael E.
Abstract Background Sentinel lymph node biopsy remains controversial for cutaneous melanoma of the head and neck (CMHN). Incidence and factors associated with recurrence after negative sentinel lymph node biopsy have not been well delineated. Methods Characteristics of 204 patients with head and neck melanoma who had a negative sentinel lymph node biopsy were studied. Main outcomes were overall survival and disease‐free survival. Results Recurrence developed in 45 patients (22%) with a median time to recurrence of 20.1 months. Five‐year overall survival was 91.8% for patients without recurrence and 57.0% for those with recurrence. The overall regional recurrence rate was 8.8% (n = 18) and was associated with Breslow thickness >2 mm and scalp location of the primary tumor. The false omission rate was 3.4%. Conclusion For CMHN, regional recurrence after negative sentinel lymph node biopsy occurs at acceptably low rates relative to other sites, although it is associated with adverse survival. © 2014 Wiley Periodicals, Inc. Head Neck37: 1116–1121, 2015